Investigating helium-layer stripping in the interacting SN 2021efd - Pyykkinen, Niko (My University, 2024)
Some stars meet their ends in supernovae (SN) explosions. Massive stars (>8M_sun) at the end of their stellar evolution suffer a core-collapse and explode as core-collapse supernovae (CCSNe). SNe have diverse observational properties and are divided into classes based on them. Much can be known about the star that exploded from the SN it produced. Stripped-envelope supernovae (SESNe) are explosions of massive stars that lost a part of the hydrogen envelope (Type IIb), the whole hydrogen envelope (Type Ib), or the hydrogen envelope and the helium layer (Type Ic). Evidence has accumulated to support a binary interaction as the stripping mechanism for the hydrogen envelope. The mechanism responsible for the helium-layer stripping for the progenitors of Type Ic SNe is still an open question. In this thesis, I performed an in-depth analysis of the spectroscopic and photometric data of the peculiar Type Ib SN 2021efd. The light curve of SN 2021efd has an excess at late phases compared to the level that is expected from the decay of Nickel-56. I analyzed the spectra of SN 2021efd and concluded that the excess luminosity was caused by interaction of the ejecta with hydrogen-poor circumstellar material. I derived the ejecta parameters and the progenitor star mass and concluded that they do not separate SN 2021efd from the general population of SESNe. I estimated the mass-loss rate of the progenitor star by comparing the interaction luminosity in SN 2021efd to numerical calculations. Based on the high mass-loss rate, I concluded that the mass-loss mechanism is not consistent with line-driven wind. Instead, I suggest that the mass loss could have happened in eruptions. Based on the high mass-loss rate, I concluded that the mass-loss mechanism is not consistent with line-driven wind. Instead, I suggest that the mass loss could have happened in eruptions.
Keywords: Supernovae, supernova progenitors, core-collapse supernovae, stripped-envelope supernovae, interacting supernovae, SN 2021efd, mass-loss mechanism, helium stripping, light curve model